Isometric Stretch Alters Vascular Reactivity of Mouse Aortic Segments - De Moudt, Sofie; Leloup, Arthur; Van Hove, Cor; De Meyer, Guido; Fransen, Paul (Frontiers in Physiology, 2017)
Most vaso-reactive studies in mouse aortic segments are performed in isometric conditions and at an optimal preload, which is the preload corresponding to a maximal contraction by non-receptor or receptor-mediated stimulation. In general, this optimal preload ranges from about 1.2 to 8.0 mN/mm, which according to Laplace´s law roughly correlates with transmural pressures of 10 to 65 mmHg. For physiologic transmural pressures around 100 mmHg, preloads of 15.0 mN/mm should be implemented. The present study aimed to compare vascular reactivity of 2 mm mouse (C57Bl6) aortic segments preloaded at optimal (8.0 mN/mm) versus (patho)physiological (10.0-32.5 mN/mm) preload. Voltage-dependent contractions of aortic segments, induced by increasing extracellular K+, and contractions by 1-adrenergic stimulation with phenylephrine (PE) were studied at these preloads in the absence and presence of L-NAME to inhibit basal release of NO from endothelial cells (EC). In the absence of basal NO release and with higher than optimal preload, contractions evoked by depolarization or PE were attenuated, whereas in the presence of basal release of NO PE-, but not depolarization-induced contractions were preload-independent. Phasic contractions by PE, as measured in the absence of external Ca2+, were decreased at higher than optimal preload suggestive for a lower contractile SR Ca2+ content at physiological preload. Further, in the presence of external Ca2+, contractions by Ca2+ influx via voltage-dependent Ca2+ channels were preload-independent, whereas non-selective cation channel-mediated contractions were increased. The latter contractions were very sensitive to the basal release of NO, which itself seemed to be preload-independent. Relaxation by endogenous NO (acetylcholine) of aortic segments pre-contracted with PE was preload-independent, whereas relaxation by exogenous NO (diethylamine NONOate) displayed higher sensitivity at high preload. Results indicated that stretching aortic segments to higher than optimal preload depolarizes the SMC and causes Ca2+ unloading of the contractile SR, making them extremely sensitive to small changes in the basal release of NO from EC as can occur in hypertension or arterial stiffening.